Contract Law and the Governance of Inter‐Firm Technology Partnerships – An Analysis of Different Modes of Partnering and Their Contractual Implications* - Hagedoorn, John; Hesen, Geerte (Journal of Management Studies, 2007)
abstract This paper studies some major legal implications of inter‐firm technology partnering through equity joint ventures, non‐equity partnerships, and licensing contracts. These different partnerships are placed within the classical and relational contracting perspectives, while also considering intellectual property rights issues. Samples of contracts of partnerships in bioscience, fine chemicals, biotechnology and biopharmaceuticals are analysed, in detail, with reference to the distribution of property rights, major contractual clauses, and measures for conflict resolution. Equity joint ventures and non‐equity partnerships are found to largely follow a relational contracting perspective, while licensing contracts are governed by a classical contracting perspective.